Eight Channel Temperature Monitoring using Thermocouple Sensors (type K) Based on Internet of Thing using ThinkSpeak Platform - Candra Prastyadi; Bedjo utomo; Her Gumiwang Ariswati; Dyah Titisari; Sumber Sumber; A. Senthil Kumar (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
A laboratory incubator is a device used to incubate a breed. a very important condition in the procedure Incubator is the optimal temperature conditions for microorganisms to grow. The incubator is equipped with a temperature controller so that the temperature can be adjusted according to the breed to be raised. Incubators use an oven like dry heat. The purpose of this study was to test and analyze the accuracy of the thermocouple sensor with incubator media in a laboratory incubator calibrator. The main design method uses the 8 MAX 6675 module, the 8 K type Thermocouple module, Arduino Mega, and SD Card data storage. Temperature measurements were measured with a Type K thermocouple sensor. The thermocouple sensor has 8 channels which function to measure the temperature at each camber point of the incubator. The temperature will be stored on the SD card for data analysis and the data can be processed in graphical form. Benchmarking is done using a temperature data logger. This is done so that the design results are below the standard comparison tool. The measurement results on the module compared to the comparison tool obtained the largest error value, namely 3.98%, namely on channel T6 at 35°C with ordinary incubator media and the smallest error on ordinary incubator media at point T6 at 37°C, which is 0.06 % and at 35 C the temperature of the incubator fan has the largest error of 2.98% and the smallest error of 0.86%. the module can perform well by testing the comparison tool at every point